PENGARUH PERSEPSI DAN SIKAP PEMAIN TERHADAP NIAT MENGGUNAKAN MOBILE GAME MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL - Putu Adi Putra Arimbawa; Surachman Surachman; Ananda Sabil Hussein (Universitas Mercu Buana, 2017)
Abstract: Technology Acceptance Model was developed in order to describe therelationship between user’sperceptive and their attitude toward an object. This researchmain purpose is to analyze the relationship between mobile game’s player’s perceptiveand their attitude toward the game and finally how that relationship affect user’sintention to use newer game. The research conducted in Indonesia and using purposivesampling, we have collected data from 170 Clash of Clan players. We use Partial LeastSquare (PLS) as our data analysis technique. This research results are user’s perceptive(perceived usefulness and perceived ease of use) both has direct significant effecttoward attitude and intention to use. In addition, direct significant effect also foundbetween attitude and intention to use, which made attitude toward use could becomemediated variable between the relationship between users’s perceptive and user’sintention to use. This research contribution is giving a good description for theimportance role of user’s attitude toward product use to improve user’s intention to usethe product.Keywords: TAM, User’s Perception, User’s Attitude, User’s Intention, Mobile Game